2015
DOI: 10.3390/ijms17010004
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Characterization and Expression Pattern Analysis of a Cytosolic Copper/Zinc Superoxide Dismutase (SaCSD1) in a Highly Salt Tolerant Mangrove (Sonneratia alba)

Abstract: Mangroves are critical marine resources for their remarkable ability to tolerate seawater. Antioxidant enzymes play an especially significant role in eliminating reactive oxygen species and conferring abiotic stress tolerance. In this study, a cytosolic copper/zinc superoxide dismutase (SaCSD1) cDNA of Sonneratia alba, a mangrove species with high salt tolerance, was successfully cloned and then expressed in Escherichia coli Rosetta-gami (designated as SaCSD1). SaCSD1 comprised a complete open reading frame (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Generally, the CuZnSOD contains three conserved motifs defined as CuZnSOD signature motifs; these signature motifs KAVAVL, F(L)HL(I)HQ(A)F(L)GDTTNGC, and GNAGGRLACGVV(I)GL were also identified in the CeCSD1 and CeCSD2 proteins (Figures and ). These were in accordance with previous findings, indicating that these sites and motifs are essential for the structure and function of CuZnSOD and may be involved in stabilizing SOD conformation under harsh environmental conditions …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Generally, the CuZnSOD contains three conserved motifs defined as CuZnSOD signature motifs; these signature motifs KAVAVL, F(L)HL(I)HQ(A)F(L)GDTTNGC, and GNAGGRLACGVV(I)GL were also identified in the CeCSD1 and CeCSD2 proteins (Figures and ). These were in accordance with previous findings, indicating that these sites and motifs are essential for the structure and function of CuZnSOD and may be involved in stabilizing SOD conformation under harsh environmental conditions …”
Section: Resultssupporting
confidence: 93%
“…Comparisons of CeCSDs with other CuZnSODs revealed that the C‐terminal was more conserved than the N‐terminal. These findings suggest that they may have functions similar to those of other SODs …”
Section: Resultsmentioning
confidence: 69%
“…It reaches an optimal growth in 5 to 50% seawater, indicating its capacity to tolerate high salinity and hypoxia [19]. It can synthesize organic solutes to adjust cellular osmotic potential and produce antioxidant enzymes for scavenging reactive oxygen species (ROS) against high salinity [20]. Therefore, it is an attractive ecological model to investigate genetic mechanisms underlying salt adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Mangroves are critical marine resources for their remarkable ability to tolerate seawater and are uniquely adapted to tropical and subtropical coasts [ 1 ]. Mangrove forests played an important role in ecosystem services and supported coastal livelihoods, yet they are relatively low in the number of species [ 2 ].…”
Section: Introductionmentioning
confidence: 99%